(untitled) (Purbanchal University Health Journal, 2024)
Acute compartment syndromes of the upper arm following trauma is even though a less common complication, it certainly is an orthopedic emergency that requires prompt diagnosis and intervention, typically via surgical decompression by fasciotomy. I report a 45 years old factory worker with compartment syndrome after trauma treated with fasciotomy. The limb was saved and wound was closed serially by shoelace technique. At 6 months follow up visit, the patient was asymptomatic with 30 to 150 degrees of ac-tive range of movement on examination. In this article I emphasize on early identification and management of acute compartment syndrome.